Propuesta para mejorar la producción y rentabilidad de la finca San Fernando del cantón Sozoranga - Vásquez Soto, Miguel Antonio (2014)
The countries of Latin America are by nature purely agricultural nations , where much of the population invest their resources to such activities. In our country, agricultural production is generating significant income in the processes of social development , and in many cases the effect of uneven development of misuse of existing resources , mainly affecting the most vulnerable sectors , including small producers. In the canton Sozoranga , farms and ranches are not handled under technical , with the San Fernando one of many in the sector in which there is no tech management , especially where livestock operations are performed empirically , by so production is low, added to it an account of existing resources and consequently does not take no production profitability . This research will be carried out in order to improve the production and profitability of the San Fernando with the approach of alternative production tech . Also contributing to the agricultural sector to small , medium and large producers Canton Sozoranga with the spread of the proposal to be implemented . The proposal aims to fulfillment of the following objectives listed below are disclosed : • Improve production and farm profitability San Fernando Canton Sozoranga . • Perform administrative and production assessment of the farm to determine their agricultural components each . • Discuss strategies to improve the San Fernando As a strategy for the faithful fulfillment of the above objectives , it is necessary to develop previously established methodological processes that respond to the same set of variables which are mentioned below : • Diagnosis of the farm : Diagnosis : Strengths - Weaknesses - Opportunities - Threats . • Projection of the farm : Mission, Vision and Objectives . • Selection Strategies . • Project Selection : general and operational program. As results of the final analysis of the research , it was determined that the San Fernando is not driving technical management processes of production, such situations being a reflection of administrative oversight for which you are enrolled .